El Hierro Island Global Geopark Diversity of Volcanic Heritage for Geotourism - Dóniz-Páez, Javier; Pérez, Nemesio M. (Geoheritage, Geoparks and Geotourism, 2023)
This open access book explores El Hierro Island, which is geologically the youngest of the Canary Islands (Spain). Having registered its latest volcanic eruption in 2011-2012, it is an oceanic subtropical island with low population pressure and a largely unchanged natural landscape. Accordingly, a great geodiversity of volcanic morphologies and erosion processes has been preserved. In addition, half of the land is protected as a Biosphere Reserve and as a UNESCO Global Geopark, and the island is pursuing energy self-sufficiency. Local tourism is a sustainable activity, as the main attractions are either diving or hiking through the island's various volcanic landscapes. Covering these and other aspects, and using accessible language, the book will appeal to scientists specialized in geotourism, active leisure entrepreneurs, and members of the general public interested in volcanic geoheritage and geotourism.